Analysis of Factors Affecting Investment Decisions and its Implications on Organizational Performance - Mulyadi Mulyadi; Tri Widyastuti; Zulkifli Zulkifli (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Investment refers to the act of allocating capital with the expectation of generating a rate of return in the future. The process of making investment decisions entails a cognitive assessment that involves choosing one alternative from a range of options based on available information. Given the highly competitive global business environment, investors are compelled to thoroughly study and develop their intuition to make informed investment choices. The objective of this study is to analyze the determinants influencing Investment Decisions, which are proxied by Financial Literacy, Financial Behavior, Risk Perception, and Overconfidence, and their implications on Organizational Performance. The selection of research subjects in the Jakarta Industrial Estate Pulogadung area is based on the Government's plan to relocate to Subang, West Java. The study employs primary quantitative data collected through non-probability sampling and purposive sampling methods, and utilizes Structural Equation Model - Partial Least Square (SEM-PLS) analysis with SmartPLS 4 software. The findings of the analysis reveal that Financial Literacy have negative effect on Investment Decisions. Conversely, Financial Behavior, Risk Perception, and Overconfidence have positive effect on Investment Decisions. Additionally, Risk Perception have positive effect on Organizational Performance. However, Financial Literacy, Financial Behavior, Overconfidence, and Investment Decisions have no effect on Organizational Performance. Consequently, it can be inferred that all factors influencing investment decisions have the capacity to influence organizational performance, an organization's overall performance cannot be solely attributed to its investment decisions, as other factors also come into play